Back Cover: Diaphragm‐based optical fiber sensor for pulse wave monitoring and cardiovascular diseases diagnosis (J. Biophotonics 10/2019). Issue 10 (2nd October 2019) - Unknown
Abstract : A wearable device based on fiber optic biosensor for high‐precision radial pulse wave monitoring and diagnosis is proposed and demonstrated in this article. Owing to the high sensitivity of the tiny fiber tip with aluminum diaphragm assembled in the sportswristband, weak acoustic signal induced by arterial pulse can be high‐fidelity recovered and then quantitatively analyzed for clinical diagnosis, which is promising in early cardiovascular diseases indicating. Further details can be found in the article by Jingyi Wang, Kewei Liu, Qizhen Sun, et al. (e201900084 ). Abstract : A wearable device based on fiber optic biosensor for high‐precision radial pulse wave monitoring and diagnosis is proposed and demonstrated in this article. Owing to the high sensitivity of the tiny fiber tip with aluminum diaphragm assembled in the sportswristband, weak acoustic signal induced by arterial pulse can be high‐fidelity recovered and then quantitatively analyzed for clinical diagnosis, which is promising in early cardiovascular diseases indicating. Further details can be found in the article by Jingyi Wang, Kewei Liu, Qizhen Sun, et al. (e201800084 ).